Hermeneutik Schleiermacher: Eksplorasi Dimensi Gramatikal dan Psikologis dalam Penafsiran Teks Al-Qur’an - Ihsyan Wahyudi (KIPS Institute, 2025)
This research discusses how to study the interpretation of the Al-Qur'an text in Schleiermacher's thinking with a focus on grammatical and psychological interpretation in discussing the interpretation of the Al-Qur'an text. The aim of this research is to discuss the focal point of the grammatical and psychological aspects of the interpretation of the Koran from Schleiermacher's perspective. The method used in this research is a qualitative method (library research) by collecting various literature from Schleiermacher's hermeneutical thought. The result of this research is Schleiermacher's Hermeneutics, which is an approach to textual interpretation introduced by Friedrich Schleiermacher in the 19th century. In the context of interpretation in the text of the Koran, Schleiermacher's hermeneutics explores grammatical and psychological dimensions to understand the meaning and message contained in the holy text. This approach plays an important role in understanding the linguistic and psychological context that involves the author and reader in the interpretive process. Through this approach, Schleiermacher's hermeneutics contributes to embracing the complexity of the Qur'an and opens up space for deeper and contextual interpretation.